INDICATORS INNOVATIONS FOR PRODUCTIVITY GAINS OF MILK CHAIN - Vendrametto, Oduvaldo; Mollo Neto, Mario; Okano, Marcelo Tsugio (Revista Brasileira de Engenharia de Biossistemas, 2010)
Milk production in Brazil is an important activity of the agricultural sector has a vital role in the process of economic and social development of the country. After half a century of stagnation, largely explained by strong government intervention in the dairy market, the chain of milk production begins in the early 90's to experience significant changes in all market segments, from production to consumption. The lack of vision and understanding of the supply chain as a whole, led to an asymmetric behavior, resulting in losses and instabilities throughout the production process, with justifiable dissatisfaction, especially small farmers. The aim of this study was to develop indicators of productive efficiency of dairy farms, associated with specific innovations to rank them on a table, or maturity model, with five levels depending on the stage of evolution of the technological contributions, inputs, skills and preparation of the flock of people. The results of analysis of data from field research pointed to the best practices that producers may have to evolve in the league table and to increase production efficiency.